Experimental testing of basic crash elements made of CFRP by additive technologies - Kalina, Tomáš; Špirk, Stanislav; Sedláček, František (Manufacturing Technology Journal, 2020)
This paper deals with the experimental testing of the basic crash element, which is made of PA6 with short carbon fiber reinforcement by additive technology. Additive technologies allow the production of very complex, thin-walled and hollow shapes, which can be used to tune the desired characteristics of the deformation member. The variable size of the deceleration, the length of the deformed portion and the total amount of energy absorbed can be controlled by suitable geometry. The initial impact peaks can be reduced by gradually changing the geometry. Experimental testing of basic crash elements was performed on several specimens and average values are used here. Primarily the maximal and average deceleration and total energy absorbed are monitored. Obtained data will be used for validation of material properties in Crash-Pam software. Using a validated material model, larg-er and more complex deformation members will be proposed, eg for the racing car Formula SAE.
Keywords: Crash element; Impact attenuator; Additive technologies; CFRP; Formula SAE